PELATIHAN KEPEMIMPINAN DASAR UNTUK MEMBENTUK JIWA KEPEMIMPINAN KERJA LAPANGAN YANG RESPONSIF DAN INOVATIF BAGI SISWA PRAKERIN - Ari Amir Alkodri; Fitriyani Fitriyani; Sarwindah Sarwindah; Marini Marini; Devi Irawan (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2024)
Leadership is something that is very necessary for a leader. This is because the leader is the highest position in the company who plays an important role in realizing the company's goals. Leadership is abstract so it can only be seen from the results, namely the results of providing motivation to employees. Without a leader who has a leadership spirit, it is impossible for a company to realize its vision and mission. Leaders must have a positive and energetic soul and have a vision and mission that is in line with the company's vision and mission. A leader must also be able to direct, organize and control all resources, both human resources (employees) and material resources so that company goals can be achieved. This training aims to provide learning related to the spirit of leadership to students so that when running an organization at school or an organization outside of school, students already understand how to be a leader (leadership) and students also understand being a responsive and innovative leader. This training is also carried out to fulfill the lecturer's obligations, namely implementing one of the tri dharmas of higher education, namely community service.